Mental disorders and lack of social support among refugees and Ugandan nationals screening for HIV at health centers in Nakivale refugee settlement in southwestern Uganda - Robin E. Klabbers; Scholastic Ashaba; Joshua Stern; Zikama Faustin; Alexander C. Tsai; Julius Kasozi; Andrew Kambugu; Peter Ventevogel; Ingrid V. Bassett; Kelli N. O'Laughlin (Journal of Global Health Reports)
# Background